A Forty Year Old Lady with Undiagnosed Lutembacher Syndrome - A Case Report - Rahman, Muhammad Ashiqur; Rahman, AKM Fazlur; Haque, Tauhidul; Banarjee, Sajal K; Hoque, Md Harisul; Sultan, Md Ashraf Uddin (University Heart Journal, 2011)
A forty years widow having four children presented with palpitation, shortness of breath on exertion and chest pain. Her sufferings progressively increase in course of time. Her ECG shows complete Right Bundle Branch Block. Transthoracic echocardiography showed atrial septal defect of secundum type. Both the leaflets of the mitral valve were thickened with mild degree of diastolic doming. Key Words: Lutembacher Syndrome; Mitral Stenosis. DOI: 10.3329/uhj.v6i1.7198 University Heart Journal Vol.6(1) 2010 pp.51-54